'Apps are cool but generally pretty pointless': LGBTIQ+ young people's mental health app ambivalence. (May 2019) - Byron, Paul
This article considers the potential development of mental health apps for LGBTIQ+ young people. It reports on data from an Australian study of LGBTIQ+ young people's mental health help-seeking experiences. Participants (aged 16–25 years) highlighted the potential value of mental health apps, yet also questioned the need for another digital intervention. Addressing stigma around mental health was seen as a greater priority for many, as was addressing the inadequate mental health information and support available to LGBTIQ+ young people through schools and mainstream health services. Participants noted that a mental health app must not only be useful, reliable and accessible but also actively sought, which was sometimes unlikely. This article questions a contemporary public health agenda for developing digital solutions to complex social problems. Furthermore, it asks whether health inequities and social stigma can be addressed by apps that typically prioritise the practice of individualised self-care.